Trabalho, produção associada e produção de saberes na comunidade tradicional Imbê-MT - Santos, Lirian Keli dos (2013)
The current scenario of structural precariousness of work, marked by rising unemployment and social exclusion, has taken workers belonging to the lower classes to seek the production of life through the popular economy. This research is a starting point to reflect on the production of knowledge of work in the Traditional Imbê-MT Community. We seek to understand the process of associated production conducted in this community as a production strategy that questions the logic of capitalism, despite being inserted in it. To develop the analysis we use historical materialism and left the category "Work", based on Marx's theoretical framework. In carrying out their work, these men and women of Traditional Community Imbê not only learn to produce goods but to produce them also produce knowledge, education, knowledge and social relations. These are the "experiential knowledge" that aim to reflect, based on assumptions made by Thompson, as well as in studies of Fischer and Tiriba because we understand that it is through work that individuals and community performing (re) construct knowledge. Research has shown that by working men and women who build / produce their lives specifically. In this study we chose the qualitative research methodology, among the possibilities we chose to develop a case study. Data were collected through direct observation of the everyday practices of individuals involved in the community. We use in-interviews (semistructured) recorded individual, seeking to highlight issues related to the life stories of workers and community workers IMBE. The analysis showed that the work associated not only emerged as a means to create jobs, but a way to live with dignity in the land they chose. However, if we widen our gaze, we realize that in the course of the proceedings that goal was exceeded, because in addition to material survival strategy, initiatives are a form of challenge to employment subject to capital. We find that the collective domain of the production process and practices with self-management features work organization were essential to the development of activities in agribusiness. We observed that the ratio of production associated Imbê community is closely linked to a conception of the world less exploratory, and that this view is related to the knowledge of the experience, because it is a traditional, family relationships, life path, and the religious question. Finally, we understand that the daily practice of these workers generate knowledge about the environment, about the world of work and how society can be organized so as to produce a living in another way, more human. The work, in this sense, is the generator of general and specific knowledge. Specific in that it focuses on the production of certain material goods for their survival, and overall because broaden the worldview of these workers, placing them in a historical time and social space.